Dated radar-stratigraphy between Dome A and South Pole, East Antarctica: old ice potential and ice sheet history - Rebecca J. Sanderson; Neil Ross; Kate Winter; Robert G. Bingham; S. Louise Callard; Tom A. Jordan; Duncan A. Young (Journal of Glaciology)
An array of information about the Antarctic ice sheet can be extracted from ice-sheet internal architecture imaged by airborne ice-penetrating radar surveys. We identify, trace and date three key internal reflection horizons (IRHs) across multiple radar surveys from South Pole to Dome A, East Antarctica. Ages of ~38 ± 2.2, ~90 ± 3.6 and ~162 ± 6.7 ka are assigned to the three IRHs, with verification of the upper IRH age from the South Pole ice core. The resultant englacial stratigraphy is used to identify the locations of the oldest ice, specifically in the upper Byrd Glacier catchment and the Gamburtsev Subglacial Mountains. The distinct glaciological conditions of the Gamburtsev Mountains, including slower ice flow, low geothermal heat flux and frozen base, make it the more likely to host the oldest ice. We also observe a distinct drawdown of IRH geometry around South Pole, indicative of melting from enhanced geothermal heat flux or the removal of deeper, older ice under a previous faster ice flow regime. Our traced IRHs underpin the wider objective to develop a continental-scale database of IRHs which will constrain and validate future ice-sheet modelling and the history of the Antarctic ice sheet.